The association between meaning in life and harmful drinking is mediated by individual differences in self-control and alcohol value. (June 2020) - Copeland, Amber; Jones, Andrew; Field, Matt
Highlights: Presence of meaning in life is negatively associated with harmful drinking. Searching for meaning in life is positively associated with harmful drinking. Self-control and value of alcohol mediate the associations between meaning and harmful drinking. These psychological mechanisms underlie transitions out of harmful drinking with meaning in life. Abstract: Introduction: The adoption of adult roles that provide meaning in life is associated with reduced harmful drinking. The current study examined whether this relationship is mediated by increased self-control and reduced value of alcohol. Methods: Cross-sectional design. 1043 adults (786 females) ≥18 years old completed an online survey. The outcome variable was scores on the Alcohol Use Disorders Identification Test (AUDIT), predictor variables were presence of and search for meaning in life (Meaning in Life Questionnaire), and mediating variables were trait self-control (Brief Self-Control Scale) and the value of alcohol (Brief Assessment of Alcohol Demand). Results: Presence of meaning in life had a significant negative association ( B  = −0.01, SE = 0.00, 95% CI −0.02 to −0.00, p  = .015), whilst search for meaning in life had a significant positive association ( B  = 0.01, SE = 0.00, 95% CI 0.01 to 0.02, p  = .001) with AUDIT scores. The negative association was mediated by increased self-control ( B  = −0.09, SE = 0.01, 95% CI −0.12 to −0.06) and decreased value of alcohol ( B  = −0.02, SE = 0.01, 95% CI −0.04 to 0.00), whilst the positive association was mediated by decreased self-control ( B  = 0.05, SE = 0.01, 95% CI 0.03 to 0.07) and increased value of alcohol ( B  = 0.02, SE = 0.01, 95% CI 0.00 to 0.04), thereby supporting our hypotheses. Conclusions: The relationships between presence and search for meaning in life and harmful drinking are mediated by individual differences in both trait self-control and the value of alcohol.